2003
DOI: 10.1016/s0006-3495(03)75007-3
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Cu(II) Binding of Prion Protein Variants Related to Inherited Human Prion Diseases

Abstract: All inherited forms of human prion diseases are linked with mutations in the prion protein (PrP) gene. Here we have investigated the stability and Cu(II) binding properties of three recombinant variants of murine full-length PrP(23-231)-containing destabilizing point mutations that are associated with human Gerstmann-Sträussler-Scheinker disease (F198S), Creutzfeld-Jakob disease (E200K), and fatal familial insomnia (D178N) by electron paramagnetic resonance and circular dichroism spectroscopy. Furthermore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
48
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 63 publications
10
48
0
Order By: Relevance
“…Furthermore, addition of a peptide encompassing the amino acid residues 112-125 to cerebellar cultures in parallel with PrP121-231 neutralises the toxicity of PrP121-231. [11,13] These biological results show that it is quite possible that potentially toxic regions of the C-terminal domain can be masked by other hydrophobic residues in the rest of the protein and that only an aberrant folding or assembly of the protein exposes them to the environment. Thus, taking into account that the helix II prion domain is a highly competitive anchoring site for copper(ii), changes its conformation from a-helix to b-sheet after copper binding, and can interact with artificial membranes, we can speculate that this domain is not normally available to interact with the metal due the masking effect of other regions belonging to the flexible part of the same protein or to other partners.…”
Section: Peptide Interactions With Artificial Membranesmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, addition of a peptide encompassing the amino acid residues 112-125 to cerebellar cultures in parallel with PrP121-231 neutralises the toxicity of PrP121-231. [11,13] These biological results show that it is quite possible that potentially toxic regions of the C-terminal domain can be masked by other hydrophobic residues in the rest of the protein and that only an aberrant folding or assembly of the protein exposes them to the environment. Thus, taking into account that the helix II prion domain is a highly competitive anchoring site for copper(ii), changes its conformation from a-helix to b-sheet after copper binding, and can interact with artificial membranes, we can speculate that this domain is not normally available to interact with the metal due the masking effect of other regions belonging to the flexible part of the same protein or to other partners.…”
Section: Peptide Interactions With Artificial Membranesmentioning
confidence: 97%
“…[10] In addition to the copper(ii) binding in the unstructured amyloidogenic region, it has been reported that Cu 2 + coordinates to the structured C-terminal domain mPrP121-231, which contains three histidine residues, although spectroscopic approaches did not allow the determination of the coordination environment or the location of the binding sites of the three copper(ii) complex species formed at different pHs. [11][12][13] A few studies have been carried out on copper(ii) interactions with peptides in the domains of the three helices of PrP. [9,14] Among these, the peptide PrP178-193 (DCVNITIKQHTVTTTT), which corresponds to the helix II, has been found to promote copper(ii)-induced lipid peroxidation and cytotoxicity in primary neuronal cultures, while the analogous PrP180-193 (VNITIKQHTVTTTT) forms amyloid, as evidenced by electron microscopy and Congo Red birefringence.…”
Section: Introductionmentioning
confidence: 99%
“…Conformational studies on binding of Cu 2ϩ to PrP in vitro have been performed using peptides (26 -28) or truncated variants of PrP (29 -31) and at nonphysiological temperatures (2,10,(13)(14)(15)(16)(17) and in water or buffers of low ionic strength (3,9,13,(32)(33)(34). We have used full-length PrP to investigate conformational changes and aggregation upon Cu 2ϩ -binding at physiological temperature (37°C).…”
mentioning
confidence: 99%
“…1. In addition, experimental evidence (28,29) indicates that the structured C terminus is capable of binding Cu 2ϩ as well. These binding sites were very recently investigated (30) theoretically by using QM/MM Car-Parinello molecular dynamics.…”
mentioning
confidence: 99%